Cab45 deficiency leads to the mistargeting of progranulin and prosaposin and aberrant lysosomal positioning. (6th January 2023) - Tran, Mai Ly; Tüshaus, Johanna; Kim, Yeongho; Ramazanov, Bulat R.; Devireddy, Swathi; Lichtenthaler, Stefan F.; Ferguson, Shawn M.; von Blume, Julia
Abstract: The trans‐Golgi Network (TGN) sorts molecular "addresses" and sends newly synthesized proteins to their destination via vesicular transport carriers. Despite the functional significance of packaging processes at the TGN, the sorting of soluble proteins remains poorly understood. Recent research has shown that the Golgi resident protein Cab45 is a significant regulator of secretory cargo sorting at the TGN. Cab45 oligomerizes upon transient Ca 2+ influx, recruits soluble cargo molecules (clients), and packs them in sphingomyelin‐rich transport carriers. However, the identity of client molecules packed into Cab45 vesicles is scarce. Therefore, we used a precise and highly efficient secretome analysis technology called hiSPECs. Intriguingly, we observed that Cab45 deficient cells manifest hypersecretion of lysosomal hydrolases. Specifically, Cab45 deficient cells secrete the unprocessed precursors of prosaposin (PSAP) and progranulin (PGRN). In addition, lysosomes in these cells show an aberrant perinuclear accumulation suggesting a new role of Cab45 in lysosomal positioning. This work uncovers a yet unknown function of Cab45 in regulating lysosomal function. Abstract : Proposed model of sorting of lysosomal proteins in wild‐type (left) and Cab45 deficient cells (right). Under wild‐type conditions, Cab45 might support the receptor‐cargo interaction of sortilin (depicted as zoom). Lysosomal proteins PSAP and PGRN can be recognized and bound by their receptors and sorted into endolysosomal structures (light red circle) before maturing to their processed forms in lysosomes (purple circle). Results from this study indicate that in Cab45 deficient cells, the recognition of sortilin and its cargo is decreased, leading to increased trans‐ Golgi export and secretion of immature lysosomal protein PSAP (hypersecretion). PSAP can be partially sorted by the interaction with PGRN to the endolysosomal route.